Insecticide Treatment and Physiological Quality of Seeds - Dan, Lilian Gomes de Moraes; Dan, Hugo de Almeida; Braccini, Alessandro de Lucca e; Barroso, Alberto Leão de Lemos; Ricci, Thiago Toshio; Piccinin, Gleberson Guillen; Scapim, Carlos Alberto (IntechOpen, 2012)
None